Data‐adaptive longitudinal model selection in causal inference with collaborative targeted minimum loss‐based estimation. Issue 1 (6th November 2019) - Schnitzer, Mireille E.; Sango, Joel; Ferreira Guerra, Steve; van der Laan, Mark J.
Abstract: Causal inference methods have been developed for longitudinal observational study designs where confounding is thought to occur over time. In particular, one may estimate and contrast the population mean counterfactual outcome under specific exposure patterns. In such contexts, confounders of the longitudinal treatment‐outcome association are generally identified using domain‐specific knowledge. However, this may leave an analyst with a large set of potential confounders that may hinder estimation. Previous approaches to data‐adaptive model selection for this type of causal parameter were limited to the single time‐point setting. We develop a longitudinal extension of a collaborative targeted minimum loss‐based estimation (C‐TMLE) algorithm that can be applied to perform variable selection in the models for the probability of treatment with the goal of improving the estimation of the population mean counterfactual outcome under a fixed exposure pattern. We investigate the properties of this method through a simulation study, comparing it to G‐Computation and inverse probability of treatment weighting. We then apply the method in a real‐data example to evaluate the safety of trimester‐specific exposure to inhaled corticosteroids during pregnancy in women with mild asthma. The data for this study were obtained from the linkage of electronic health databases in the province of Quebec, Canada. The C‐TMLE covariate selection approach allowed for a reduction of the set of potential confounders, which included baseline and longitudinal variables.